Effect of Blower Power and Engine Speed Variations on Engine Component Temperatures Fueled by B40 and Off-Grade CPO - Maulana, Ivan; Saputro, Wilianadi; Saputro, Erwan (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
This study examines the effect of blower power variation and engine speed on the temperature of diesel engine components fueled by B40 and off-grade Crude Palm Oil (CPO). The experiment was conducted using a Kubota RD 65 DI-NB diesel engine with a constant electrical load of 4 kW at two engine speeds: 1200 and 2000 RPM. The off-grade CPO was preheated to 100°C, while B40 was used without any special treatment. The blower air supply was varied from 0% to 100% to evaluate its impact on the engine’s thermal behavior. The results indicate that increasing blower power up to 100% causes a rise in temperature in the cylinder head, cylinder block, exhaust pipe, and coolant tank, whereas a decrease in temperature is observed in the intake pipe. Under all engine speed conditions, engines fueled with off-grade CPO showed higher average temperatures compared to those using B40, with increases of 4.81% in the cylinder head, 8.47% in the cylinder block, 10.16% in the intake pipe, 6.86% in the exhaust pipe, and 5.81% in the coolant tank. These temperature increases are attributed to the higher oxygen content and viscosity of off-grade CPO, which lead to larger fuel droplets and incomplete combustion, thereby increasing deposit formation. These findings highlight the significant influence of fuel characteristics and air supply on the thermal performance of diesel engines.